Analisis Varians Biaya Produksi Sebagai Alat Untuk Mengukur Tingkat Efisiensi Biaya Produksi Pada UD. Kamang Wangko: Production Cost Variance Analysis as a Tool for Measuring the Level of Production Cost Efficiency At UD. Kamang Wangko - Charmelia Sophia Timpulu; Sintje Rondonuwu; Lady Diana Latjandu (Universitas Sam Ratulangi, 2023)
This study aims to determine the variance analysis of production costs as a tool to measure the level of efficiency of production costs at UD. Kamang Wangko. The type of research used is qualitative descriptive data. Data obtained by conducting direct interviews and observations. The results of this study indicate that the calculation of production costs using variance analysis shows a favorable or profitable difference. Variance analysis of raw material costs obtained a difference of Rp.15,815,000 variance analysis of direct labor costs obtained a difference of Rp. 4,100,000 and variance analysis of factory overhead costs obtained a difference of Rp. 3,782,538